Synthesis and characterization of star-shaped copolymers obtained from lactic acid and heterocyclic monomers - Florjańczyk, Z.; Frydrych, A.; Chudzik, A.; Rucińska, K.; Basamon, M. (Polimery, 2021)
In this paper we report a two-step method of synthesis of star-shaped copolymers of lactic acid and heterocyclic monomers. Firstly, the branched cores with hydroxyl end groups have been obtained by the polycondensation of L or D-lactic acid with pentaerythritol. Then we carried out ring opening polymerization of trimethylenecarbonate or L-lactide in the presence of star-shaped poly(lactic acid) cores and tin(II) 2-ethylhexanoate as a catalyst. We proved that setting the polymerization temperature at 130 °C provides a block structure of obtained copolymers. However, increasing temperature could cause transesterification and consequently changes in the chain structure. The results of the DSC analysis indicate that the block copolymer, consisting of the poly(lactic acid) and the polytrimethylenecarbonate segments, forms a homogeneous amorphous phase, whereas stereoblock poly(lactic acid) forms a crystalline phase which has a melting point between 180 and 190 °C.